FINES, FEES, AND FORFEITURES - B. A. Colgan (Russian Journal of Economics and Law)
Objective: to analyze the imposition and collections of fines, fees, and forfeitures according to the legislation of the UnitedStates of America).Methods: dialectical approach to the cognition of social phenomena, allowing to analyze them in the historical development and functioning in the context of a set of objective and subjective factors, which determined the choice of the following research methods: formal-logical, comparative-legal, and sociological.Results: the use of fines, fees, and forfeitures has expanded significantly in recent years as lawmakers have sought to fund criminal justice systems without raising taxes. Concerns are growing, however, that inadequately designed systems for the use of such economic sanctions have problematic policy outcomes, such as the distortion of criminal justice priorities, exacerbation of financial vulnerability of people living at or near poverty, increased crime, jail overcrowding, and even decreased revenue. In addition, the imposition and collections of fines, fees, and forfeitures in many jurisdictions are arguably unconstitutional, and therefore create the risk of often costly litigation. This article provides an overview of those policy and constitutional problems and provides several concrete solutions for reforming the use of fines, fees, and forfeitures.Scientific novelty: for the first time, the article substantiates the necessity to eliminate poverty penalties and other policies that negatively impact ability to pay. It is proposed to create systems for meaningful consideration of financial effect of fines, fees and forfeitures; to develop non-incarcerative alternative sanctions; to restrict the use of fines, fees, and forfeitures in cases involving juveniles; to ensure that criminal justice actors are insulated from the pressure to generate revenue and from the benefits of revenue produced from those economic sanctions.Practical significance: the main provisions and conclusions of the article can be used in scientific and educational activities when considering the issues related to imposition of fines, fees, and forfeitures.